Global Anthropogenic Carbon Dioxide Emission in 2005: Environmental Kuznets Curve Hypothesis and Implications for Policy - Krishnan, T. S. (International Journal of Environment, 2016)
Environmental Kuznets Curve (EKC) hypothesis provides support for public policies that emphasize economic growth at the expense of environmental degradation. This hypothesis postulates an inverted U-shaped relationship between economic growth and environmental degradation with plausible explanations. We contribute to the discussion on EKC hypothesis by focusing on anthropogenic carbon dioxide (CO2) emission (a greenhouse gas) during an extreme year. In the year 2005, concentration of anthropogenic CO2 became higher than the natural range observed over the last 650,000 years. Using econometric modeling of data from 122 countries for the year 2005, we study the key question: Does EKC hypothesis hold for anthropogenic CO2 emission after controlling for energy consumption and environmental governance? We do not find statistical support for EKC hypothesis. But, we find that improvements in environmental governance reduces CO2 emission. This suggests support for environmental policies that specifically promote CO2 emission reduction and does not emphasize economic growth at the expense of environmental degradation. INTERNATIONAL JOURNAL OF ENVIRONMENT Volume-5, Issue-2, March-May 2016, Page: 48-60